Soil test correlation of Olsen-P for corn and soybean in a subtropical humid región - Reussi Calvo, Nahuel Ignacio (2025)
Accurate phosphorus (P) fertilizer recommendations for soybean [Glycine max (L.) Merr.] and corn (Zea mays L.) are crucial for maximizing productivity and economic return while minimizing the environmental impact of fertilizer use. Currently, there are no calibrations for diagnosing P deficiencies in croplands of Bolivia. This study aimed to define and compare the P critical soil test value (CSTV) for corn and soybean using the Olsen method. Twenty fertilization field trials were conducted for corn and 75 for soybean in the Santa Cruz de la Sierra region, including treatments with and without P fertilization. Soil pre-planting (0–20 cm) organic matter, Olsen P, pH, as well as yield were determined. Relative yield (RY) was estimated as the ratio of grain yield between the control and P-fertilized treatments. The CSTV was calculated using the arcsine-logarithm method, with data resampling through bootstrapping. The average yield response to added P was 259 kg ha−1 (+11.0%) for soybean and 545 kg ha−1 (+13.7%) for corn. For soybean, CSTVs were determined as 6.1 and 11.0 mg kg−1 (r = 0.34, p = 0.002) for 90% and 95% of RY, respectively. For corn, the CSTVs were 8.1 and 13.9 mg kg−1 (r = 0.34, p = 0.14) for 90% and 95% of RY, respectively. The confidence intervals suggest no differences between crops. The Olsen-P is a promising tool for soil fertility recommendations in Bolivia. Yet, the modest goodness of fit obtained suggests the need for further research refining the performance of soil test P diagnosis in the region.